Understanding variability in discharge planning processes for the older person. (January 2020) - Buikstra, Elizabeth; Strivens, Edward; Clay-Williams, Robyn
Highlights: Application of FRAM to hospital ward discharge planning processes. Involving staff in developing FRAM improved engagement in workplace QI activities. The method highlighted problems staff face in an increasingly complex environment. Identifying system resonance prompts change reducing the chance of adverse outcomes. Abstract: Discharge planning for the older person is complex and complicated with multiple task interactions, and multiple opportunities for the process to go right and to go wrong. The purpose of the research was to understand the variability in everyday performance during discharge processes for the older person, to identify the parts of the process that may be susceptible to resonance and other potential problems areas. The study employed mixed method data collection comprising document review, focus groups and semi-structured interviews. This research was set in a Sub-Acute Geriatric Evaluation and Management inpatient ward in a 531-bed public hospital in regional Australia. Fourteen ward staff participated in 13 semi-structured interviews. Two focus groups were held, of which the first included five business and senior clinicians who had knowledge of the business practices related to the discharge planning processes. The second focus group included five interview participants. The discharge planning processes was analysed using Functional Resonance Analysis Method (FRAM). The resultant FRAM model provided a graphical description of functional variability in the discharge planning processes. A total of 61 instances of variability were identified through the interviews and focus groups. Recommendations were developed and prioritised on each of these instances and presented to staff for implementation. It is concluded that the health care system is complex and modelling performance adjustments in everyday work provides staff at the coalface with an opportunity to highlight and resolve issues that they are continuing to face on a day-to-day basis in the workplace.